(untitled) (Eurasian Medical Research Periodical, 2022)
The Portunus armatus is a crustacean that has high economic value, and a wide geographical distribution and medicinal using and considers being sea food in many counters as Iraq. This study aimed to know the treatment effect of portunus armatus shell extract against oxidative stress and the role in histopathological treatment. The study included the 15 experimental rats aged 2-3 months distributed to three groups 5 animal of each, the first was given distilled water for four weeks as a control group, while the second group was given hydrogen peroxide at concentrations 1% for two weeks orally using gavage, the third group was given H2O2 for two weeks 1,% and then treated with Portunus armatus extract for tow week. At the end the period of the experiment the animals were scarified. The animals were dismembered, and samples from the liver and spleen were transported to the lab for analysis and tissue segmentation. For the histopathology study, liver and spleen tissues were taken, where it’s kept in formalin until the segmentation.